Does birthweight affect the mode of delivery? - (:unkn) unknown (ELSEVIER SCI IRELAND LTD, 2003)
Objective(s): To investigate whether the mode of delivery effects the birthweight. Study design: In this retrospective study, 3092 singleton live births following uncomplicated pregnancies were analyzed. Birthweights were expressed as multiples of the median (MoM) for the relevant gestational week. The birthweight of children born vaginally was compared with those born by cesarean section. Results: The birthweight of children born vaginally was lower than that of those born by cesarean section. However, this difference was not observed at all gestational ages. Increasing cesarean rates and birthweights throughout years were observed, and the women, who delivered by cesarean section, were older than those, who delivered vaginally. Conclusion(s): It appears that mode of delivery has negligible effect on birthweight. (C) 2003 Elsevier Science Ireland Ltd. All rights reserved.
Keywords: birthweight; cesarean section; vaginal delivery; CENTILES